Effect of ligand binding on the buoyant density of DNA in Nycodenz gradients. - Ford, T C (1984)
The effect of ligand binding upon the buoyant density of DNA in Nycodenz gradients has been studied using DNAs of differing base compositions. The effect of both intercalating ligands (ethidium bromide and proflavin) and non-intercalating ligands (distamycin A, DAPI and netropsin) has been studied. The binding of intercalating ligands to DNA has essentially no effect on the buoyant density of DNA in Nycodenz gradients. The non-intercalating ligands were found to increase the buoyant density of DNA in a base specific manner. The increase in buoyant density can be interpreted in terms of disruption of the hydration shell of the DNA molecule caused by the binding of the ligand along the minor groove of the DNA helix.